Fitting of the In Vitro Gas Production Technique to the Study of High Concentrate Diets - Zahia Amanzougarene; Manuel Fondevila (Animals, 2020)
In vitro rumen fermentation systems are often adapted to forage feeding conditions, with pH values ranging in a range close to neutrality (between 6.5 and 7.0). Several attempts using different buffers have been made to control incubation pH in order to evaluate microbial fermentation under conditions simulating high concentrate feeding, but results have not been completely successful because of rapid exhaustion of buffering capacity. Recently, a modification of bicarbonate ion concentration in the buffer of incubation solution has been proposed, which, together with using rumen inoculum from donor ruminants given high-concentrate diets, allows for mimicking such conditions in vitro. It is important to consider that the gas volume recorded is in part directly produced from microbial fermentation of substrates, but also indirectly from the buffering capacity of the medium. Thus, the contribution of each (direct and indirect) gas source to the overall production should be estimated. Another major factor affecting fermentation is the rate of passage, but closed batch systems cannot be adapted to its consideration. Therefore, a simple semicontinuous incubation system has been developed, which studies the rate and extent of fermentation by gas production at the time it allows for controlling medium pH and rate of passage by manual replacement of incubation medium by fresh saliva without including rumen inoculum. The application of this system to studies using high concentrate feeding conditions will also be reviewed here.